Cannabis use in early ADHD, a 3-years follow-up study in relations to clinical characteristics - L.R. Kvitland; H. Moa; J. Schei; S. Lydersen; P. Thomsen; I. Mundal (European Psychiatry, 2022)
Introduction ADHD is known to increase the risk of substance use, and is associated with lower degrees of education, criminal behavior and neuropsychic difficulties. Previous research is limited by small samples, variable findings, and short follow-up time. Earlier research tends to be limited to substance use above the threshold for abuse or dependency.